ENERGY CHALLENGES, ENERGY OPPORTUNITIES (Utah Environmental Law Review; Vol 29 No 1 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} I want to start with a brief parable. About six weeks ago, two residents of Salt Lake City, Thomas Garner and his wife Tamitha, drove down to photograph some wild horses in Nevada. They drove to Cedar City, and then they went west. They got in a blizzard, and they got stuck. Their Dodge Dakota came to a halt in a big snowdrift. They got stranded. Some of you have read this story. They had, maybe ten gallons of gasoline in the pickup. They had some food they had bought. They practiced radical energy conservation, and twelve days later they walked out alive. They stayed with the pickup for nine days. They were in no hurry to get off of oil. They were not worried about their carbon footprint. They were eating granola bars and running the engine for brief periods of time to stay warm. When they were down to granola bars and some dog food, Tamitha suggested that maybe it was time to start walking. Her husband, who was an eagle scout, remembered seeing on TV that you could take the seat cushions out of a vehicle and turn them into snowshoes. He strapped the seat cushions to his feet with bungee cords and they walked for three days. They had a lighter and some carburetor cleaner. They used the carburetor cleaner to start fires at night and slept under trees. When they met a snowplow on day twelve, after everyone had given them up for dead, they were in fine form. Their relatives said this was a miracle, but I do not think this was due to divine intervention. I think these two people practiced a kind of energy intelligence. They passed an energy IQ test that is similar in many respects to what the nation faces today. We live in an amazing time in human history. I think we Americans really do not fully understand how blessed we are to be alive right now.